Pengaruh Sistem Pengendalian Intern Terhadap Kualitas Akuntabilitas Keuangan - Aristanti Widyaningsih (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2015)
This study aims to measure the effect of the implementation of the internal control system (which consists of the control environment, risk assessment, control activities, information and communication, and monitoring) partially and simultaneously to the quality of the financial accountability of schools. This research is exploratory. Population sampling of this research is all elementary schools in the city of Bandung. The sampling technique used is the Convenience Sampling. A large sample of questionnaires collected and can be processed in this study amounted to 168. The data collected in this study are primary data. Data analysis techniques used in this study is Path Analysis Techniques (Path Analysis). Simultaneous testing results show that the system of internal control schools (which consists of the control environment, risk assessment, control activities, information and communication, and monitoring) significantly affects financial accountability. Partial test results showed that only the control environment, control activities and monitoring significant effect on financial accountability. While the other dimension, namely risk assessment, information and communication is not significant